Thomas Pynchon - Battesti, Anne; C. Lento, Stephen; Chamerois, Gilles; Chorier-Fryd, Bénédicte; Henson, Nicholas; Herman, Luc; Hollander, Charles; Kolbuszewska, Zofia; Maisonnat, Claude; McAvan, Em; Mösch, Matthias; Paul Eve, Martin; et al. (Horizons anglophones, 2021)
Thomas Pynchon was born on May 8,1937 in Glen Cove. Long Island, New York. He started his writing career in his high school days, published his early stories in a series of magazines, came to fame in 1963 with his first novel, V., and has since been consistently praised as one of the major American writers of all times. The papers in this volume address all of Thomas Pynchon’s works to date, from his earliest production in Voice of the Hamster to Inherent Vice. The collection brings together fifteen specialists from three continents-America. Australia and Europe. They contribute to the current debates on Pynchon’s supposed ’post modernism, either by revitalizing established postmodern critical perspectives and applying them to seldom read texts, or by reappraising Pynchon’s fiction within broader literary and philosophical contexts. Though individual approaches vary, common concerns are expressed, among which a marked interest in the reappraisal of ethical and political dimensions, as well as a focus on the questions of return and the potential emergence of the new out of the old.
Keywords: Literature American; Literature (General); politique; éthique; Thomas Pynchon; postmodernisme; littérature américaine contemporaine; roman historiographique; oeuvres de jeunesse; post-mimétique; contemporary American fiction; postmodernism; historiographic fiction; politics; ethics; early works; post-mimetic